Direct contact ultrasound assisted freezing of mushroom (Agaricus bisporus): Growth and size distribution of ice crystals - Islam, M.; Zhang, M.; Fang, Zhongxiang; Sun, J. (Elsevier Ltd, 2015)
To reduce the size of ice crystals in mushroom (Agaricus bisporus) contact ultrasound (300 W, 20 kHz) was applied during freezing and frozen storage. Stereomicroscopy was used to observe the ice crystal morphology, and DSC and NMR spectroscopy were performed to evaluate the water states in the samples. Results indicated that ultrasound irradiation initiated the nucleation of ice and reduced the mean size of ice crystals during freezing and frozen storage, and therefore improved the frozen product quality compared to the control samples. Most of the ice crystals in the ultrasound assisted frozen (UAF) samples were in the size range of 0-80 microns while that for the control samples were in the size range of 50-180 microns. SEM photos also proved that due to the application of ultrasound, the sizes of the ice crystals was reduced. This micro-scale information on the documentation of ice crystals will assist in understanding the ice crystal growth phenomena in an ultrasound assisted freezing process.